IMPLEMENTATION OF LITERACY CULTURE TO IMPROVE CHEMISTRY LEARNING OUTCOMES - Siregar, Tiurlina; Simorangkir, Agustina (Jurnal Ilmu Pendidikan Indonesia, 2025)
This study aims to examine the influence of the implementation of literacy culture on improving chemistry learning outcomes in class X students of SMA Negeri 7 Jayapura. In this context, the School Literacy Movement (GLS) is required to foster a culture of reading non-lesson books for 10-15 minutes before learning starts. The method used is purposive sampling, with data collection techniques in the form of questionnaires (questionnaires) for literacy culture and cognitive tests for learning outcomes. The results of the study show that the implementation of literacy culture in class X of SMA Negeri 7 Jayapura can improve chemistry learning outcomes with an average n-gain value of 0.52 which is in the medium category. However, the results of correlation and regression analysis showed that the literacy culture variable (X3) had a nonsignificant effect on learning outcomes (Y). The correlation coefficient (R) is very low, which is 0.005.